KONSISTENSI PASAL 284 KUHP TERHADAP UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 - Ismayawati, Any (Faculty of Law, University of Muhammadiyah Malang, 2016)
Adultery issue has been regulated in Article 284 of the Indonesian Criminal Code. However, in its implementation, vigilantism is more widely used by the community in response to the suit. In short it can be said that Article 284 of the Criminal Code is not effective in combating the crime of adultery. Article 284 of the Criminal Code, both legally and philosophically opposed to the values contained in Article 29 Paragraph (1) of Indonesian Constitution. In juridical, adultery prohibition in the norms of religion in Indonesia not only in people who already tied a marital relationship. In philosophy, the prohibition of adultery in the norms of religion in Indonesia is not only to provide protection to the institution of marriage, but also protect the sanctity of sexual relations, nasab, individual honour and even social honour. It can be said that the prohibition of adultery in religious norms is a form of protection against social honor as well as protection against